The research and implementation continuum of biofortified sweet potato and maize in Africa - Tanumihardjo, Sherry A.; Ball, Anna-Marie; Kaliwile, Chisela; Pixley, Kevin V. (Wiley, 2017)
The enhancement of sweet potato and maize with provitamin A carotenoids has been part of HarvestPlus's research continuum since the formation of the biofortification project. This review includes case studies of biofortification strategies used for sweet potato in Uganda and orange maize in Zambia. The current status of the science and release of biofortified varieties was reviewed by three scientists who were part of the HarvestPlus program for more than a decade with input from a scientist who experienced orange maize dissemination in Zambia. High β‐carotene varieties of sweet potato were introduced into South Africa and Mozambique, and efficacy and effectiveness studies, respectively, showed promise to improve vitamin A status, followed by dissemination efforts in Uganda. A randomized, controlled effectiveness trial tested extension models to promote sweet potato and assessed vitamin A intake among Ugandans. Orange maize breeding was initially a challenge, but considering that the carotenoid biosynthetic pathway was present in maize germplasm, breeders quickly bred higher amounts of provitamin A into the maize that was ultimately released in Zambia. Initial resistance occurred because orange maize was associated with yellow maize, which had negative connotations associated with food aid and animal feed, and consumers preferred white maize. Currently, both orange crops are available on the market.